2017
DOI: 10.1007/s40430-017-0808-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of C/H on the radiative and thermal behavior of liquid fuel flames and pollutant emissions

Abstract: radiation of the flame. The flame luminosity was increased by 66% when the C/H was increased from 5.47 to 5.68, whereas the flame thermal radiation increased by 26%. In addition, a new correlation is proposed to predict the linear relation of the increase in the thermal radiation and the increase in the luminosity of the flame as a function of C/H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nanoemulsion fuel is composed of kerosene as the base fuel, silver–water nanofluid, and surfactant. The chemical composition of kerosene as determined by a CHNS elemental analyzer VARIO ELCUBE is given in Table …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoemulsion fuel is composed of kerosene as the base fuel, silver–water nanofluid, and surfactant. The chemical composition of kerosene as determined by a CHNS elemental analyzer VARIO ELCUBE is given in Table …”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition of kerosene as determined by a CHNS elemental analyzer VARIO ELCUBE is given in Table 1. 49 All glassware was washed in a mixture of distilled water and nonionic detergent, which was followed by rinsing with distilled water and ethanol many times to make sure of removing any remains of the nonionic detergent. The glassware was afterward dried to be ready for use.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings revealed that the introduction of carbon in the form of nanoparticles led to an increase in reaction rates, a reduction in flame length, elevated temperatures, and enhanced thermal radiation. Moreover, an increase in carbon in the form of heavier fuel resulted in slower combustion, longer flame length, increased temperatures, and heightened thermal radiation [20]. Pourhosseini et al (2017) investigated how injecting silver nanoparticles could improve thermal characteristics and decrease pollutants in liquid fuel flames [21].…”
Section: Introductionmentioning
confidence: 99%